Penerapan Teknologi Tepat Guna dalam Peningkatan Produksi Kopi Wilis di BUMDesa Barokah Desa Ngebel, Kabupaten Ponorogo, Jawa Timur: The Application of Appropriate Technology in Improving the Coffee Production of Wilis Coffee at BUMDesa Barokah, Ngebel Village, Ponorogo Regency, East Java - Saputra, Anggara Wiyono Wit; Sugiarto, Sugiarto; Widhiyanuriyawan, Denny; Setyono, Langgeng; Nugroho, Arief Budi (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
This community service activity is carried out to improve the quality of life for the people of Ngebel Village, Ponorogo Regency, by applying appropriate technology in coffee production. Ngebel Village is known as a producer of Wilis coffee, which has great potential but still faces issues in post-harvest processing that are not yet efficient. This activity aims to improve the productivity and quality of Wilis coffee by implementing modern coffee hulling and grinding machines. The methods used in this activity include a functional approach and mentoring, with the application of appropriate technology in the form of coffee hulling and grinding machines specifically designed to enhance production efficiency. Training is conducted to ensure that the BUMDesa managers can operate and maintain the machines properly. After implementing these machines, there is expected to be a significant increase in the efficiency of coffee processing, a reduction in production costs, and an improvement in the quality of Wilis coffee. The community will also acquire new skills in operating post-harvest coffee technology. Additionally, this activity helps improve the competitiveness of Wilis' coffee products in the market. By applying appropriate technology in coffee production at BUMDesa Barokah in Ngebel Village, the main goal of sustainable activity will be achieved: improving the quality and efficiency of coffee production, which contributes to the economic well-being of the local community.